2013
DOI: 10.1080/02699931.2012.732040
|View full text |Cite
|
Sign up to set email alerts
|

The effect of object–valence relations on automatic evaluation

Abstract: Two experiments tested the effect of co-occurrence of a target object with affective stimuli on automatic evaluation of the target when the relation between the target and the affective stimuli suggests that they have opposite valence. Participants learned about targets that ended an unpleasant noise or a pleasant music. The valence of such targets is opposite to the valence of the affective stimuli that co-occur with them. Participants reported preference for targets that ended noise over targets that ended m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
196
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(211 citation statements)
references
References 19 publications
12
196
3
Order By: Relevance
“…Support for that possibility comes from the finding that both automatic and deliberate evaluation are reversed after people receive new information that changes the meaning of earlier information (Mann & Ferguson, 2015;Wyer, 2010). Perhaps only when the validity information is not explicit (e.g., Moran & Bar-Anan, 2013;, validity is not used immediately for revising evaluations, new evaluative associations are not formed, and automatic/deliberate discrepancy emerges.…”
Section: Explanations For the Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Support for that possibility comes from the finding that both automatic and deliberate evaluation are reversed after people receive new information that changes the meaning of earlier information (Mann & Ferguson, 2015;Wyer, 2010). Perhaps only when the validity information is not explicit (e.g., Moran & Bar-Anan, 2013;, validity is not used immediately for revising evaluations, new evaluative associations are not formed, and automatic/deliberate discrepancy emerges.…”
Section: Explanations For the Resultsmentioning
confidence: 97%
“…Previous research found that when explicit information about the validity of the co-occurring affective stimuli is presented before or immediately after presenting the co-occurrence, validity information has the same effect on automatic and deliberate evaluation (Boucher & Rydell, 2012;Peters & Gawronski, 2011;Siegel, et al, 2012). If delayed validity information also has the same influence on automatic and deliberate evaluation, the only relevant evidence left for different effects of evaluative learning on automatic versus deliberate evaluation would come from studies that did not explicitly inform participants that the cooccurrence information is not valid (e.g., Moran & Bar-Anan, 2013).…”
Section: Explanations For the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are affected by recent information, especially newly presented propositional information, and are related to high level cognition like inference of the relationships among given information 7. Therefore, the same learning experience can have different effects on implicit and explicit attitudes 8. Furthermore, they can affect each other during their formation 3…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, I appeal to research on both implicit and explicit prejudice, and I believe we should draw the same general lessons for addressing both types of problematic attitude. Nevertheless, it is true that certain specific manipulations are more effective for changing implicit than explicit attitudes, and vice versa (see, e.g., Rydell et al 2006;Moran & Bar-Anan 2013), so interventions must be designed Consider, for example, structural factors contributing to racial inequality. Elizabeth Anderson (2012a: 171) argues that "the structural ground" of persistent racial inequalities is not widespread racism, but ongoing de facto segregation in housing, education, employment, electoral districts, and so on.…”
Section: Arguments For Prioritizing Structural Changementioning
confidence: 99%